Morphological and microstructural characterization of laser-glazedplasma-sprayed thermal barrier coatings - Ribeiro, R. M. (2006)
Laser glazing has been revealing a high potential for the improvement of plasma-sprayed (PS) thermal barrier coatings (TBCs) by reducing surface roughness, eliminating open porosity on the surface and generating a controlled segmented crack network, although the relationship of the processing parameters with the resultant properties has not yet been completely established. In this investigation, TBCs consisting of atmospheric plasma-sprayed (APS) ZrO2–8wt.%Y2O3 were subjected to a CO2 continuous wave laser-glazing process in order to seal its surface porosity, generating an external dense layer. For that purpose, different amounts of radiation resulting from different scanning speeds were applied to the specimens as well as different track overlapping. Results have shown a significant decrease of the surface roughness after the laser treatment. All specimens presented a fully dense and porous free external layer with a polyfaceted columnar microstructure highly adherent to the plasma-sprayed coating. Controlled surface crack networks, extremely dependent on the laser scanning speed and track overlapping, were achieved for each set of processing parameters. The cracks were found to have a tendency to be oriented in two perpendicular directions, one in the direction of the laser-beam travel direction, the other perpendicular to it. Moreover, the cracks parallel to the beam travel direction are found to be on the overlapping zone, coinciding with the edge of the subsequent track. The cracks are perpendicular to the surface along the densified layer and tend to branch and deviate from the vertical direction below it, within the porous PS coating. XRD results revealed mainly tV nontransformable tetragonal zirconia with a small percentage of residual monoclinic zirconia for the as-sprayed coating. All glazed coatings presented only tV nontransformable tetragonal zirconia with some variations on preferable crystal orientation. Grain sizes varied from 26 to 52 nm, increasing with an increase of laserirradiated energy; microstrain behaved inversely.